Racial and Ethnic Disparities in Years of Potential Life Loss Among Patients With Cirrhosis During the COVID-19 Pandemic in the United States. (13th April 2023) - Zhao, Yunyu; Yeo, Yee Hui; Samaan, Jamil; Lv, Fan; He, Xinyuan; Liu, Jinli; Li, Mei; Gao, Ning; Park, Justin; Yang, Ju Dong; Ayoub, Walid S.; Zhang, Lei; et al.
Abstract : INTRODUCTION: Our aim was to evaluate the impact of race/ethnicity on cirrhosis-related premature death during the COVID-19 pandemic. METHODS: We obtained cirrhosis-related death data (n = 872, 965, January 1, 2012–December 31, 2021) from the US National Vital Statistic System to calculate age-standardized mortality rates and years of potential life lost (YPLL) for premature death aged 25–64 years. RESULTS: Significant racial/ethnic disparity in cirrhosis-related age-standardized mortality rates was noted prepandemic but widened during the pandemic, with the highest excess YPLL for the non-Hispanic American Indian/American Native (2020: 41.0%; 2021: 68.8%) followed by other minority groups (28.7%–45.1%), and the non-Hispanic White the lowest (2020: 20.7%; 2021: 31.6%). COVID-19 constituted >30% of the excess YPLLs for Hispanic and non-Hispanic American Indian/American Native in 2020, compared with 11.1% for non-Hispanic White. DISCUSSION: Ethnic minorities with cirrhosis experienced a disproportionate excess death and YPLLs in 2020–2021.